2009
DOI: 10.1016/j.jss.2008.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Estradiol-Treated Mesenchymal Stem Cells Improve Myocardial Recovery After Ischemia

Abstract: Preischemic infusion of MSCs protects myocardial function and viability. E2-treated MSCs may enhance this paracrine protection, which suggests that ex vivo modification of MSCs may improve therapeutic outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
31
0
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(37 citation statements)
references
References 37 publications
3
31
0
3
Order By: Relevance
“…8,32,36 Estrogen increases protein S-nitrosylation, a common posttranslational protein modification, 37 and reduces inflammatory markers 32,38 and afterload-or agonist-induced cardiac hypertrophy via the inhibition of calcineurin hypertrophic transcription factor and mitogen-activated protein kinase signaling pathways. 39 Estrogen also improves endothelial and myocardial function after ischemia by an antiapoptotic and pro-survival effect on cardiomyocytes, 40,41 endothelial progenitor cell mobilization 42 and mesenchymal stem cell-mediated vascular endothelial growth factor release. 43,44 These rapid effects of estrogen on the action of CF6 were not examined in this study.…”
Section: Discussionmentioning
confidence: 99%
“…8,32,36 Estrogen increases protein S-nitrosylation, a common posttranslational protein modification, 37 and reduces inflammatory markers 32,38 and afterload-or agonist-induced cardiac hypertrophy via the inhibition of calcineurin hypertrophic transcription factor and mitogen-activated protein kinase signaling pathways. 39 Estrogen also improves endothelial and myocardial function after ischemia by an antiapoptotic and pro-survival effect on cardiomyocytes, 40,41 endothelial progenitor cell mobilization 42 and mesenchymal stem cell-mediated vascular endothelial growth factor release. 43,44 These rapid effects of estrogen on the action of CF6 were not examined in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with male MSCs, vascular endothelial growth factor (VEGF) production was significantly higher and expression of proinflammatory cytokines, TNF-α and IL-6 significantly lower in female MSCs induced by lipopolysaccharide (LPS) and hypoxia [15,16]. Additionally, estrogen-treated MSCs provoke significantly higher VEGF production, and the hearts infused with estrogen-treated MSCs exhibited convincingly greater left ventricular developed pressure (LVDP) and improved contractility and compliance compared to the hearts with estrogen-untreated MSCs or vehicles, which suggests that estrogen may have indirect cardioprotective effects via enhancement of MSCs paracrine pathways [17]. It is well known that macrophages and cardiomyocytes release proinflammatory cytokines following injury.…”
Section: Effects Of Estrogen On Cardiac Repair After Ischemic Infarctionmentioning
confidence: 99%
“…However, there has been increasing concern over the low rate of engraftment of transplanted stem cells as a majority of them are lost within a few days of transplantation (2,31,39,43). To counter such loss upon transplantation, MSCs have been preconditioned in several ways, including hypoxic preconditioning (HPC), to enhance the retention and survival of these cells in the MI heart (12,16,18,41,42). In our earlier studies we observed that the ischemic region in the infarct heart of murine models could reach an oxygen level as low as 0.2% (4,25), which would imply that the survival and proliferation of transplanted stem cells in the infarct tissue would require the cells to adapt to very low oxygen tension in the infarct heart.…”
mentioning
confidence: 99%